Deconstructing Colonial Misconceptions Potlatch Ceremonies of Kwakwaka’wakws First Nations in Life Writing and Fictional Discourses - Mrozek-Granieczny, Hanna (Romanica Silesiana)
For centuries, Western culture (mis)represented and appropriated the First Nations. Aboriginal peoples were regarded either as primitive, animal-like savages, or they were romanticised and eroticised in order to justify the Canadian policy of civilisation and assimilation of the natives into the monolithic “Britain of the North.” Even though since the time of the signing of the Multiculturalism Act, the concept of Canadian identity has been undergoing major changes embracing racial and cultural minorities, native people still have to fight for recognition and their rightful place in the Canadian discourses. The problem of misrepresentation of indigenous cultures has not been eradicated. This article focuses on the analysis of the potlatch ceremonies of the Kwakwaka’wakws. Using the postcolonial perspective and methodology, it explores both the past and the contemporary culture of potlatches. It also examines the colonial misconceptions of potlatch ceremonies and the current revival of the Kwakiutl potlatching. This postcolonial analysis shows the subversion of the colonial “truths” and looks at the revival of Kwakiutl culture as the aboriginal way of re-reading and re-writing of Canadian history, deconstructing conservative national mythologies and fighting for recognition by the Canadian discourse. The following analysis also reveals changing attitudes toward Kwakwaka’wakws’ potlatches and the evolution of opinions regarding this ceremony. The discussion is based mainly on selected published official government documents, books, life writing and information obtained from a personal interview gathered by the author during her research trip to British Columbia in March 2010 (Student Mobility grant obtained by the Canadian Studies Centre, University of Silesia). Key words: the potlatch, Kwakwaka’wakws, Kwakiutls, First Nations.